1989
DOI: 10.1038/342440a0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression of human hepatocyte growth factor

Abstract: Hepatocyte growth factor (HGF) is the most potent mitogen for mature parenchymal hepatocytes in primary culture, and seems to be a hepatotrophic factor that acts as a trigger for liver regeneration after partial hepatectomy and liver injury. The partial purification and characterization of HGF have been reported. We have demonstrated that pure HGF from rat platelets is a new growth factor effective at concentrations as low as 1 ng ml-1. The effects of HGF and epidermal growth factor (EGF) are additive. The act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
1,235
0
7

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 2,060 publications
(1,260 citation statements)
references
References 18 publications
8
1,235
0
7
Order By: Relevance
“…Human recombinant HGF was purified from the conditioned medium of Chinese hamster ovary cells transfected with human HGF cDNA (Nakamura et al, 1989;Seki et al, 1990). Polyclonal antibody against human HGF was prepared from the serum of a rabbit immunized with human recombinant HGF and IgG was purified using protein A-Sepharose (Pharmacia Biotech, Uppsala).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human recombinant HGF was purified from the conditioned medium of Chinese hamster ovary cells transfected with human HGF cDNA (Nakamura et al, 1989;Seki et al, 1990). Polyclonal antibody against human HGF was prepared from the serum of a rabbit immunized with human recombinant HGF and IgG was purified using protein A-Sepharose (Pharmacia Biotech, Uppsala).…”
Section: Methodsmentioning
confidence: 99%
“…Hepatocyte growth factor (HGF), initially identified and cloned as a potent mitogen for hepatocytes (Nakamura et al, 1984(Nakamura et al, , 1989Miyazawa et al, 1989), is a stromal-derived multi-potent factor that exhibits mitogenic, motogenic, and morphogenic activities. Accumulating evidence has shown that HGF plays a distinct role in tumour-stromal interactions (Seslar et al, 1993;Rosen et al, 1994;Matsumoto et al, 1996;Inoue et al, 1997;Nakamura et al, 1997;Jiang et al, 1999).…”
mentioning
confidence: 99%
“…In vivo, MET function is particularly important for the regeneration of the liver and the kidney in response to both acute and chronic insults. Production of HGF increases steeply following liver damage, and the ensuing activation of MET in hepatocytes provides strong mitogenic and antiapoptotic stimuli for organ repair 14,15,124 . Accordingly, conditional deletion of MET in the liver results in impaired organ reconstitution after toxic insult and hepatectomy 125,126 (Fig.…”
Section: Met Signalling In Development and Diseasementioning
confidence: 99%
“…This is triggered by extracellular stimuli that regulate the activity of several transcription factors that, in turn, modulate the expression of a number of proteins, ranging from cytoskeletal and cell-cell junctional components to cell cycle regulators and anti-apoptotic effectors 9, 10 . One major environmental inducer of invasive growth is hepatocyte growth factor (HGF, also known as scatter factor), the ligand for the MET tyrosine kinase receptor (also known as the HGF receptor) 11,12,13,14,15,16,17,18,19,20 (Box 1). MET function is required for various morphogenetic events in both embryonic and adult life 21,22 and it drives the malignant progression of several different types of tumours 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The cDNAs coding for HGFL and macrophage stimulating protein (MSP) have been found to code for the same protein Bezerra et al, 1993;Shimamoto et al, 1993;Yoshimura et al, 1993). HGFL and HGF have the same domain composition with four kringle domains followed by a serine proteaselike domain and are approximately 40% identical at the amino acid level (Yoshimura et al, 1993;Nakamura et al, 1989;Degen et al, 1991;Han and Degen, 1993). HGFL induces a change in shape of mouse peritoneal macrophage, stimulates resident peritoneal macrophage to undergo a chemotactic response to endotoxinactivated mouse serum, causes marked macrophage spreading and morphological changes in vitro, stimulates ingestion of sheep erythrocytes opsonized with IgM anti-Forssman antibody and mouse C3b, and inhibits cytokine-or endotoxin-induced expression of the inducible nitric oxide synthase Skeel, 1976, 1978;Skeel and Leonard, 1994;Skeel et al, 1991;Wang et al, 1994).…”
Section: Introductionmentioning
confidence: 99%